A vehicle recall index and the sales impact by type of recall. (2018) - Richardson, Robert; Shin, Heechang; Soluade, Oredola
A vehicle recall index is created to measure the safety provided by a vehicle. Compared to J. D. Power's indices, the newly created index provides additional, useful information for consumers to use when buying a car. The importance of recall information is reflected in the negative impact on sales. The impact is measured using an event study methodology to evaluate the sales loss and time to recover from a major recall. The effect of two types of recalls is compared: 1) Toyota's unintentional problem from a defective gas pedal design causing injuries; 2) Volkswagen's intentional modification of the emission control unit to report false information resulting in no injuries. The model indicates that Toyota's sales declined for the subsequent five months, while Volkswagen's sales were affected for eleven months. The conclusion is that consumers responded more to the Volkswagen 'cheating' scandal in their purchase of a new car.